2020
DOI: 10.1038/s41598-020-61097-w
|View full text |Cite
|
Sign up to set email alerts
|

Active inference under visuo-proprioceptive conflict: Simulation and empirical results

Abstract: It has been suggested that the brain controls hand movements via internal models that rely on visual and proprioceptive cues about the state of the hand. In active inference formulations of such models, the relative influence of each modality on action and perception is determined by how precise (reliable) it is expected to be. The 'top-down' affordance of expected precision to a particular sensory modality is associated with attention. Here, we asked whether increasing attention to (i.e., the precision of) vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 75 publications
1
30
1
Order By: Relevance
“…First, there are other ways, in addition to moving our eyes, in which we can influence our visual environment. For instance, we could move our hands in our field of view (Limanowski and Friston, 2020). We could go further and move objects around in the environment or assume that other agents can do so.…”
Section: Discussionmentioning
confidence: 99%
“…First, there are other ways, in addition to moving our eyes, in which we can influence our visual environment. For instance, we could move our hands in our field of view (Limanowski and Friston, 2020). We could go further and move objects around in the environment or assume that other agents can do so.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AIF accounts of intentional reaching behavior in humans have been proposed 27 and investigated on humanoid robots 33,34 . Relevant for this work, it was shown how tuning the relative influence of the sensor modalities affected the motoric response in a hand-target phase matching in the presence of visuo-proprioceptive conflict 35 . Perceptual illusions in humans have been also investigated under this paradigm, such as the force-matching illusion 36 .…”
Section: Active Strategies For Multisensory Conflict Suppression In the Virtual Hand Illusionmentioning
confidence: 96%
“…In other words, the seen 95 and felt hand positions were always incongruent (phase-shifted) in these conditions. The delay was 96 adopted following a recent behavioral study using the similar task (Limanowski & Friston, 2020), 97 which showed that participants reliably recognized the virtual and real hand movements as 98 incongruent when applying this lag-and significant differences in behavior between conditions. 99…”
Section: Experimental Design and Procedures 65mentioning
confidence: 99%